2015
DOI: 10.1007/s00592-015-0785-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular risk factors in youth with type 1 diabetes and elevated body mass index

Abstract: Obese children with type 1 diabetes have a higher prevalence of hypertension and dyslipidemia than healthy weight children with type 1 diabetes. The possible association of obesity with lower micro-/macroalbuminuria rates warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 34 publications
(33 reference statements)
7
55
3
1
Order By: Relevance
“…The T1D Exchange recently documented that 36% of adolescents with T1D are overweight/obese [20, 21••], which is consistent with the SEARCH for Diabetes in Youth Study [22] and other US T1D samples [23, 24] but higher than the general population [25]. In addition, Canadian and Polish studies of children and adolescents with T1D found that 35 and 30%, respectively, were overweight/obese [26, 27].…”
Section: Weight Status In Type 1 Diabetessupporting
confidence: 58%
“…The T1D Exchange recently documented that 36% of adolescents with T1D are overweight/obese [20, 21••], which is consistent with the SEARCH for Diabetes in Youth Study [22] and other US T1D samples [23, 24] but higher than the general population [25]. In addition, Canadian and Polish studies of children and adolescents with T1D found that 35 and 30%, respectively, were overweight/obese [26, 27].…”
Section: Weight Status In Type 1 Diabetessupporting
confidence: 58%
“…Redondo et al found a dyslipidemia prevalence of 3.8% in the US with 11,348 T1D patients aged 2-18 years. The authors attributed this low ratio of dyslipidemia to the facts that the patients included in the study were mostly younger and highly active children and that the number of obese subjects was low [18]. In a study from Brazil, the ratio of dyslipidemia among 239 patients with T1DM was 72.5% and it was shown that dyslipidemia developed most frequently due to hypercholesterolemia and less frequently due to hyperglyceridemia.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia frequency in diabetic children varies between 3.8% and 72.5% in different studies [14][15][16][17][18][19], and hypercholesterolemia was reported as the most frequent finding [16,[19][20][21]. Redondo et al found a dyslipidemia prevalence of 3.8% in the US with 11,348 T1D patients aged 2-18 years.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between cardiac autonomic dysfunction and diabetes complications appears to begin early, as observed in adolescents with type 1 diabetes with subclinical markers of cardiovascular and renal disease . Overweight and obese in adolescents with type 1 diabetes not only have higher prevalence of cardiovascular risk factors of hypertension and dyslipidemia but also have a higher risk of albuminuria . Similarly, excess weight gain in adults with type 1 diabetes is associated with complications outcomes such as retinopathy, neuropathy, and more extensive atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%